Analisis Hukum Pidana Terhadap Penanggulangan Kejahatan Illegal Logging Di Provinsi Riau (Studi Kasus di Pengadilan Negeri Pekanbaru) - Sibarani, Anggiat; Arifin, Syamsul; Siregar, Taufik (Universitas Medan Area, 2019)
This study aims to look at one of the areas in Riau Province that is experiencing rapid forest degradation, Pekanbaru City, which is the Capital of Riau Province. The existence of forests in Pekanbaru City is only centered on the outskirts of the city and the Greater Forest Park area which is directly adjacent to the Siak Regency and urban forests which are spread in Pekanbaru City. The study was conducted in Pekanbaru City using a normative juridical approach concerning legal principles in the form of conceptions, statutory regulations, views, legal doctrines and related legal systems. This type of approach emphasizes obtaining information in the form of legal texts relating to the object under study, the data collection tool is literature study and documentation study. The results and discussion in this study found that criminal formulations against illegal logging (Illegal Loging) contained in the Criminal Code, after the enactment of Law Number 41 of 1999 concerning Forestry against acts of utilizing forest products without the permission of the authorities, legal subjects both individuals, legal entities and business entities by not providing further explanation of the formulation of criminal acts so that criminal sanctions against individuals and corporations are also applied equally to criminal sanctions, there are still many weaknesses so that they are unable or ineffective to accommodate the novelty of forest destruction. and provide a deterrent effect for the offender. Prevention and Eradication of Forest Destruction as a solution to prevent and eradicate forest destruction with a policy that is more stringent and strict criminal law.